2022
DOI: 10.7196/samj.2022.v112i5b.16072
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 response in South African communities: Screening, testing, tracing and movement modelling

Abstract: In South Africa (SA), the first case of COVID-19 was reported on 5 March 2020 from a traveller who had returned from Italy. Increases in COVID-19 cases and deaths necessitated the design and implementation of community screening, testing, and tracing as a control strategy. The SA government’s plans to implement community-based screening, testing, contact tracing and movement modelling during the early phases of the COVID-19 pandemic presented both opportunities and challenges. In this article, we present our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Since the beginning of the pandemic, South Africa reported much higher numbers of COVID-19 cases [ 16 ] than Lesotho and Zambia where our two community strategies were implemented. However, this and other studies in South Africa [ 1 , 17 , 18 ] reporting on community-based COVID-19 screening and testing did not report much detail on characteristics of participants seen and/or tested but rather reported aggregated data. Therefore, it is difficult to compare such details with the participants included in our study.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Since the beginning of the pandemic, South Africa reported much higher numbers of COVID-19 cases [ 16 ] than Lesotho and Zambia where our two community strategies were implemented. However, this and other studies in South Africa [ 1 , 17 , 18 ] reporting on community-based COVID-19 screening and testing did not report much detail on characteristics of participants seen and/or tested but rather reported aggregated data. Therefore, it is difficult to compare such details with the participants included in our study.…”
Section: Discussionmentioning
confidence: 82%
“…In other studies, an even higher number of people could be reached, and the yield was higher than what we observed in our study. A study in South Africa [ 1 ], covering all the South African provinces, reported a daily rate of 10,000 to 15,000 COVID-19 tests with a positivity rate of 19.25%. The difference observed with the findings in our study may be due to differences in the number of people targeted, the number of human resources deployed and the COVID-19 prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain health, rehabilitation and social services came to a halt as resources had to be redistributed to assist with the treatment of COVID-19 patients (Lew et al 2020 ). Because of a lack of close collaboration between sectors at all the different levels of management, the identification and agreement on what is deemed priority essential services, resulted in a breakdown in the continuity of care (Modisenyane et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%